2017
DOI: 10.1371/journal.pone.0169977
|View full text |Cite
|
Sign up to set email alerts
|

When Contact Is Not Enough: Affecting First Year Medical Students’ Image towards Older Persons

Abstract: ContextMany medical schools have initiated care internships to familiarize their students with older persons and to instil a professional attitude.ObjectiveTo examine the impact of care internships on the image that first-year medical students have of older persons and to explore the underlying concepts that may play a role in shaping this image.DesignSurvey before and after a two-week compulsory care internship using the Aging Semantic Differential (ASD; 32 adjectives) and the Attitudes toward Old People (AOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…[2][3][4][5] Conversely, studies have revealed that health professionals and students in the health field prefer not to work with the elderly. 6,7 A study involving 113 nursing students found that only 2.7% reported having interest in working with this target public, whereas 68.1% reported having no interest and the rest demonstrated neither interest nor disinterest. 6 In another study involving 100 neurologists, 77% had positive attitudes toward the elderly, 20% had negative attitudes and the remaining 3% had neutral attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Conversely, studies have revealed that health professionals and students in the health field prefer not to work with the elderly. 6,7 A study involving 113 nursing students found that only 2.7% reported having interest in working with this target public, whereas 68.1% reported having no interest and the rest demonstrated neither interest nor disinterest. 6 In another study involving 100 neurologists, 77% had positive attitudes toward the elderly, 20% had negative attitudes and the remaining 3% had neutral attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…(Rodgers -Herzog 1995: 151) Exposure to problems and difficult issues may represent an additional source of distress (cf. Kusumastuti et al 2017;White 2001), especially if, regardless of the interviewer´s own age, his or her attitudes towards old age, older people, and / or aging are inflicted with ageism. (Greenberg et al 2004) The rising numbers of older people in the global north and the quest for evidence-based policies have increased the demand for valid and reliable sociological data on various aging topics.…”
Section: Attitudes and Personality Traitsmentioning
confidence: 99%
“…A growing body of recent literature has reported that medical students and student nurses tend to have negative attitudes towards older individuals [10][11][12]. Working with older patients has often been described as a burden and as less satisfying than working with younger patients.…”
Section: Introductionmentioning
confidence: 99%